Analysis of the Public's Understanding Level Towards the Concept and Purpose of Zakat in the Modern Era - Zulinda, Nia; Elisa, Ema; Gunawan, Muhammad Wawan (Studia Economica : Jurnal Ekonomi Islam, 2024)
This research aims to analyze the public's understanding of the concept and objectives of zakat in the current modern era. This type of research is descriptive in nature, employing a qualitative approach, where it provides descriptive data on how the observed individuals speak, write, and behave. The results showed that the people already know and understand the purpose of paying zakat. Several factors influencing public understanding include zakat payments, the role of BAZNAS (National Amil Zakat Agency), zakat payment objectives, and zakat distribution. When it comes to paying zakat, people prefer to do so at mosques. The role and functions of BAZNAS are still unknown to the majority of the public due to a lack of socialization and related information. Nevertheless, people already have a thorough understanding of why they pay zakat. Regarding zakat distribution, the community believes that zakat administrators, especially those serving at the mosques where they pay zakat, are fair and accurate in distributing zakat to the deserving recipients (mustahiq). Keywords: Zakat; Public Understanding; BAZNAS